IMRT – Biomarkers for dose escalation, dose de-escalation and personalized medicine in radiotherapy for head and neck cancer. (November 2018) - Andreassen, C.N.; Eriksen, J.G.; Jensen, K.; Hansen, C.R.; Sørensen, B.S.; Lassen, P.; Alsner, J.; Schack, L.M.H.; Overgaard, J.; Grau, C.
Highlights: Radiotherapy is an integral component in the management of head and neck cancer. A notable proportion of the patients do not achieve tumor control after radiotherapy. Radiotherapy for head and neck cancer is associated with acute and late toxicity. Personalized medicine may improve the outcome after radiotherapy. Biomarkers could potentially enable individualized treatment regimens. Abstract: Radiotherapy (RT) is an integral component in the management of head and neck cancer. Despite progress in several respects, a noteworthy proportion of the treated patients do not achieve complete response after RT. Regardless of novel dose delivery technologies, RT for head and neck cancer is still associated with acute as well as late toxicity. These challenges could potentially be addressed by means of personalized treatment. In this paper, we discuss the possibilities for dose escalation, dose de-escalation and allocation to systemic concomitant treatment based on prognostic and predictive markers for tumor control as well as predictive markers for normal tissue radiosensitivity.